2010
DOI: 10.4052/tigg.22.119
|View full text |Cite
|
Sign up to set email alerts
|

My Stroll in the Backyard of Carbohydrate Chemistry

Abstract: The fields of "Glycobiology" and "Glycotechnology" are gaining an increasing amount of attention. A major part of my research has been directed at the synthesis and functional analysis of glycoconjugate oligosaccharides of various origins. In this mini-review, I wish to summarize my research history in carbohydrate chemistry of the last 12 years. Representative subjects have been 1) synthetic studies on Asn-linked glycan chains, 2) synthesis of novel glycoprotein structures, 3) approaches to polymer-support sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Using synthetic glycans and their analogues, we conducted quantitative analysis of their specific interactions with lectins, chaperones, glycosidases and glycosyltransferases (7,8). The results of interaction analysis of CRT and Fbs1 quantified by isothermal titration calorimetry revealed that these proteins can distinguish small differences in the fine structure of glycans.…”
Section: Analysis For Gqc Related Protein Using N-glycan Probesmentioning
confidence: 99%
“…Using synthetic glycans and their analogues, we conducted quantitative analysis of their specific interactions with lectins, chaperones, glycosidases and glycosyltransferases (7,8). The results of interaction analysis of CRT and Fbs1 quantified by isothermal titration calorimetry revealed that these proteins can distinguish small differences in the fine structure of glycans.…”
Section: Analysis For Gqc Related Protein Using N-glycan Probesmentioning
confidence: 99%
“…Several strategies for the synthesis of disaccharide nucleosides such as enzymatic O -glycosylation [ 20 , 21 ], chemical N -glycosylation [ 5 , 9 , 16 , 22 , 23 , 24 ] and chemical O -glycosylation [ 7 , 9 , 14 , 16 , 18 , 19 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] have been reported to date. Chemical O -glycosylation is often useful for the large-scale synthesis of the desired disaccharide nucleosides in higher chemical yields compared to chemical N -glycosylation.…”
Section: Introductionmentioning
confidence: 99%
“…The content of this review article was inspired by an outstanding contribution by Dr. Yukishige Ito, who has recently published a review in the same Journal (1). This review is primarily dedicated to contributions from our laboratory (The Glycoworld) into the field of glycosciences, which are discussed in the context of other advancements in the field of chemical synthesis with carbohydrates.…”
Section: A Introductionmentioning
confidence: 99%